Performance improvement of self-excited induction generator using capacitor bank based on PID controller - Mahdi Syukri; Ahmad Syuhada; Akhyar Akhyar; Tarmizi Tarmizi (Радіоелектронні і комп'ютерні системи)
This article discusses the operation of induction generators under fixed load and varying load conditions. One significant disadvantage of induction generators is their inherent need for reactive power. When connected to a load, it uses reactive power, and to regulate the output voltage, it requires a permanent external reactive source installed in the stator winding. Another weakness of induction generators is the instability of the voltage produced if there are fluctuations in the load being served. The goal of this research is to improve the performance of a self-excitation induction generator (SEIG) using a capacitor bank based on a PID controller. The task carried out by the controller is to maintain the SEIG output voltage at a stable voltage value during load fluctuations in the system. The PID controller regulates the reactive power supplied to the SEIG system to ensure a stable output voltage despite load fluctuations. It achieves this by adjusting the proportional, integral, and derivative actions based on the error signals.  One of the system stabilities is determined by the stability of the voltage generated. The objective of this research is to obtain a capacitor value that is appropriate to changes in the load being served so that the voltage generated has a small error percentage and the speed required to serve the load from the induction generator. The method applied in this research is to model the SEIG under load conditions connected to a capacitor bank. A capacitor bank is a source of reactive power that is added or subtracted from a system. The SEIG is modeled using MATLAB SIMULINK 2023a software and is driven by a DC motor. The output voltage of the SEIG system is input to the PID controller and the output is fed to the capacitor bank. The PID controller selects the value of the capacitor that will be injected to obtain a constant voltage value. The research results show that the SEIG system with a PID controller can control or maintain its output voltage at the initial voltage or a new steady voltage within the required error percentage range. The error percentage for the peak and rms (root rean square) voltage) is in the range of 0 % to 2 %. It can be concluded that the SEIG system with a PID controller has good performance and is in a stable condition when there are fluctuations in the load served by the generator. It is hoped that the system created can be applied to small-scale power generators in rural areas.